Characterization of adsorbent from pineapple peel waste for adsorption of Fe(III) - N. F, Abd Ghapar; Rozaimi, Abu Samah; Sunarti, Abd Rahman (IOP Publishing, 2020)
The present study explores the capability of pineapple peel, an agricultural effluent, to be converted into adsorbent targeted for the removal of Fe(III). The adsorbent was prepared from pineapple peel waste using a chemical activation method impregnated with zinc chloride (ZnCl2), and the morphological and functional characterization of the adsorbent was performed using BET, FTIR, and SEM. SEM images show rough surfaces of raw pineapple peel and has creases. However, after the chemical treatment, the surface of the adsorbent appears to be highly cave-like and porous due to the removal of substances such as pigments, gum, and other acid-soluble oligosaccharides. Raw pineapple peel contained more functional groups, including O–H stretching vibration at 3300 cm−1 and C–H vibration at 2917 cm−1, compared to the adsorbent with the disappearance of some distinctive peaks. The ability of the adsorbent to remove Fe(III) ions at different contact times and adsorbent dosages was studied. As the contact time and adsorbent dosage increased, the adsorption capacity also increased. The results provide the evidence to support the potential use of pineapple peel waste as an effective adsorbent for the treatment of wastewater in removing of Fe(III) ions